Mortality rates of acute types of coronary artery disease and sudden cardiac death in the Russian regions in 2019-2021 - I. V. Samorodskaya; M. G. Bubnova; O. A. Akulova; N. I. Ostroushko; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To compare standardized mortality rates (SMR) from acute types of coronary artery disease (CAD) and sudden cardiac death (SCD) with an assessment of their regional variability in the Russian Federation in 2019-2021.Material and methods. Rosstat data on the average annual population and the number of deaths in one-year age groups for 2019-2021 in 82 Russian subjects from acute types of CAD and SCD were analyzed using following ICD-10 codes: I21.0-9 (acute primary) myocardial infarction (MI), I22.0-9 (recurrent MI), I20, I24.1-9 (other forms of acute coronary artery disease), I46.1 (SCD). SMR was calculated based on the European standard per 100,000 population. Average regional SMR values (M±SD), coefficients of variation (СV), nonparametric Wilcoxon T-test with Bonferroni adjustment were calculated (differences were considered significant at р<0,05).Results. The average regional values of SMR from the sum of causes (acute types of CAD and SCD for 2019, 2020 and 2021) did not change significantly and amounted to 52,3±33,72; 53,84±36,17; 53,58±34,55, respectively. The annual increase in the average regional SMR for this period was noted from acute MI — 23,59±11,01; 24,85±10,92; 25,73±11,38, and other OF CAD — 19,47±26,17, 19,78±27,45; 20,54±26,79, respectively, in 2019, 2020 and 2021. A significant decrease in SMR occurred only from recurrent MI: from 7,19±5,38 to 6,97±5,97 in 2019-2020 (p=0,048) and to 4,99±4,25 in 2021 (p=0,023 to 2020). In 18 constituent entities of the Russian Federation, an annual decrease in SMR was noted, and in the rest — multidirectional changes. The increase in SMR from acute MI took place in 23 subjects of the Russian Federation with a minimum CV in 2020 and 2021 (44%). The maximum CV for SMD was recorded in 2021 (169%).Conclusion. Mortality from acute types of CAD and SMD for 2019-2021 in the Russian Federation was characterized by a stable level and high regional variability. The problem of improving the criteria for establishing acute types of CAD and SMD as the initial cause of death remains relevant in the absence or insufficiency of data for universal criteria for MI.